Scaffold-Induced Diketopyrrolopyrrole Molecular Stacks in a Covalent Organic Framework - Rager, Sabrina (Chem Mater, 2019)
[Image: see text] In recent years, covalent organic frameworks (COFs) have attracted considerable attention due to their crystalline and porous nature, which positions them as intriguing candidates for diverse applications such as catalysis, sensing, or optoelectronics. The incorporation of dyes or semiconducting moieties into a rigid two-dimensional COF can offer emergent features such as enhanced light harvesting or charge transport. However, this approach can be challenging when dealing with dye molecules that exhibit a large aromatic backbone, since the steric demand of solubilizing side chains also needs to be integrated into the framework. Here, we report the successful synthesis of DPP2-HHTP-COF consisting of diketopyrrolopyrrole (DPP) diboronic acid and hexahydroxytriphenylene (HHTP) building blocks. The well-known boronate ester coupling motif guides the formation of a planar and rigid backbone and long-range molecular DPP stacks, resulting in a highly crystalline and porous material. DPP2-HHTP-COF exhibits excellent optical properties including strong absorption over the visible spectral range, broad emission into the NIR and a singlet lifetime of over 5 ns attributed to the formation of molecular stacks with J-type interactions between the DPP subcomponents in the COF. Electrical conductivity measurements of crystalline DPP2-HHTP-COF pellets revealed conductivity values of up to 10(–6) S cm(–1).